Management of Asymptomatic Severe Degenerative Mitral Regurgitation. Issue 5 (2nd November 2017) - Lancellotti, Patrizio; Go, Yun Yun; Dulgheru, Raluca; Marchetta, Stella; Radermecker, Marc; Sugimoto, Tadafumi
ABSTRACT: The decision for surgery in the management of asymptomatic severe degenerative mitral regurgitation (MR) is about doing the right thing at the right time and place. European and American guidelines have provided us with guidance on surgical indications, albeit with different levels of recommendations. However, the timing for surgery especially in asymptomatic patients not meeting Class I indications for intervention, i.e. no evidence of left ventricular dysfunction is still avidly debated. In this review, we will present the literature on the indications and timing of surgical intervention in asymptomatic severe MR, covering guidelines from both societies. We will also touch on the emerging role of other imaging techniques, biomarkers and exercise stress testing. Finally, we will present arguments for and against both management strategies, i.e. early surgery and watchful waiting. To summarize, the management of patients with asymptomatic severe degenerative MR should be a joint decision between all members of the Heart Team and tailored according to the availability of surgical expertise, patient's surgical risk and patient's wishes.